E-Estonia: The e-government cases of Estonia, Singapore, and Curaҫao - Goede, Miguel (Archives of Business Research, 2019)
Purpose – The purpose of this article is to study how Estonia became one of the frontrunners of e-government and to answer the questions: how did Estonia do it, and can other countries do it too? The case of e-Estonia is compared to the cases of Singapore and Curaҫao. Methodology – The paper draws on literature concerning e-Estonia and e-government. Estonia and Singapore are compared, and an assessment is done to see if the island of Curaҫao can implement e-government like Estonia and Singapore did. Findings – All countries are unique and have to find their own path towards e-government. E-government is not a destination but a journey. Although all paths are unique, there are similarities, and countries can learn from each other. Originality – There are not many studies comparing e-Estonia to Singapore or other smart nations. This study also presents some lessons other countries might learn and apply on their own journey.